2013
DOI: 10.1111/sdi.12162
|View full text |Cite
|
Sign up to set email alerts
|

New Techniques for Determining the Longitudinal Effects of Local Hemodynamics on the Intima‐Media Thickness in Arteriovenous Fistulae in an Animal Model

Abstract: Remodeling in the arteriovenous fistulas (AVFs) is believed to be a hemodynamic-driven process, which results in extreme changes in the diameter and intima-media thickening (IMT) of vessels over time. This study aims to describe the successful development of techniques that enabled correlation of changes in local and longitudinal wall shear stress (WSS) with the temporal variations of the diameter and IMT in the venous segment of AVFs. An AVF was created between the femoral artery and vein of a 50-kg pig. We h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…Currently, there is no consensus on the physiologically relevant level of OSI with respect to causing damage to the endothelium, but similar OSI peaks to our mouse AVF vein at Day 7 and Day 21 (0.4, Fig. 7) were seen in the vein wall of a porcine AVF model (>0.3) [8]. …”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Currently, there is no consensus on the physiologically relevant level of OSI with respect to causing damage to the endothelium, but similar OSI peaks to our mouse AVF vein at Day 7 and Day 21 (0.4, Fig. 7) were seen in the vein wall of a porcine AVF model (>0.3) [8]. …”
Section: Discussionsupporting
confidence: 52%
“…The creation of the arteriovenous anastomosis (connection of low-pressure vein to the high-pressure arterial system) results in an immediate increase in blood flow and wall shear stress (WSS) through the AVF inflow artery and outflow vein. Computational fluid dynamic (CFD) modeling of WSS has previously been reported in porcine AVF models [7, 8] and recently in human AVF [9, 10], using non-contrast MRI, computed tomography scans, or three-dimensional ultrasound imaging protocols to obtain information needed for CFD modeling. These previous human and porcine CFD studies had temporal and spatial resolutions of on the order of 5 μm and 1 ms. A murine model has the advantage of readily available genetic manipulation by knockout and overexpression to investigate the mechanisms of AVF maturation failure.…”
Section: Introductionmentioning
confidence: 99%
“…(A) Surgical configuration of AVFs created between the femoral arteries and veins of pigs, (B) CT scan of the AVF, (C) reconstructed geometry of AVF from CT scan, and (D) Doppler ultrasound(18,19,21).…”
mentioning
confidence: 99%
“…Several studies have reported that regions with high wall shear stresses (in the range of [5][6][7][8][9][10] correspond to NIH formation [4,5,6]. On the other hand, Krishnamoorthy et al has suggested an inverse correlation between wall shear stress (in the range of 5-80 Pa during peak flow) and stenosis formation [7].…”
Section: Introduction (749 Words)mentioning
confidence: 99%